Study of Dyspepsia in a General Practice as Assessed by Endoscopy and Radiology. Issue 5938 (26th October 1974) - Barnes, R. J.; Gear, M. W. L.; Nicol, A.; Dew, A. B.
Abstract : Fifty consecutive patients presenting in a general practice with dyspepsia were studied. Each patient was referred for a combined barium-meal examination and cholecystogram, followed by fibreoptic endoscopy of the oesophagus, stomach, and duodenum. Thirty patients had a specific lesion of the upper digestive tract and a further four had gall-bladder disease; of these, 16 required surgical treatment. Endoscopy in the remaining 16 patients showed nine with mucosal abnormalities, leaving only seven patients to be classified as normal. The advantage of having an endoscopy service to supplement radiological investigation of dyspepsia is shown.